2018
DOI: 10.3390/nano8110904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conductive Material Morphology on Spherical Lithium Iron Phosphate

Abstract: As an integral part of a lithium-ion battery, carbonaceous conductive agents have an important impact on the performance of the battery. Carbon sources (e.g., granular Super-P and KS-15, linear carbon nanotube, layered graphene) with different morphologies were added into the battery as conductive agents, and the effects of their morphologies on the electrochemical performance and processability of spherical lithium iron phosphate were investigated. The results show that the linear carbon nanotube and layered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Incorporating conductive carbon into electrode materials is an effective method for drastically reducing impedance and enhancing the battery's performance [47,48] . While preparing pellets, we optimized the addition of pPDA within the range of 0–40 % (denoted as NTO/Gr+PA%) in terms of impedance, Young's modulus, micromorphology, crystal structure, and electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating conductive carbon into electrode materials is an effective method for drastically reducing impedance and enhancing the battery's performance [47,48] . While preparing pellets, we optimized the addition of pPDA within the range of 0–40 % (denoted as NTO/Gr+PA%) in terms of impedance, Young's modulus, micromorphology, crystal structure, and electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The cycling performance and rate capability of the LiFePO 4 cathodes with different binary conductive compositions are shown in Figure 7. It can be found that the electrodes with binary conductive agents displayed better electrochemical performance than those with SP only, while the electrodes with the CNT-GN combination achieved both high capacity and good cycling stability (Figure 7a-c), which may be related to their respective merits and the synergistic effect [38,54]. Based on Figure 7b, as expected, the electrode with 5% GN (SP-GN-5:5) showed the highest reversible capacity, but the electrode capacity dropped sharply with further increase in the GN content (SP-GN-3:7), probably due to the steric effect from the large planar structure of GN nanosheets [55].…”
Section: Electrochemical Performancementioning
confidence: 99%
“…And the mechanism for enhancing the electrical conductivity of the electrodes is based on forming conduction bridges among active material particles. In this regard, a range of carbon materials such as carbon black (Super-P, SP), conducting graphite, and acetylene black are commonly adopted as the conductive agents to increase the capacity, rate capability, and cycling performance of the cathode system [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has reported that conductive agents could be used as the mediator [31] to form a conductive network in electrodes, reducing the contact resistance of the electrode and improving the electron transport rate. Commercial carbon black, such as acetylene black (AB) and Super-P (SP), have been used as conductive agents in LIBs [32,33]. Compared with AB and SP, Ketjen Black (KB) has the advantages of large specific surface area, excellent electrical conductivity, and relatively narrow pore size distribution, when used as the conductive agent [34].…”
Section: Introductionmentioning
confidence: 99%